Language, Religion and Culture as Tools for Peaceful Co-Existence: A Case Study of South-Western Nigeria - Ajibade, Mufuliat Iyabode; Komolafe-Johnson, Comfort Bukola; Issah, Jimoh Atolagbe (European Scientific Journal, ESJ, 2023)
Nigeria and the world at large has experienced series of conflicts which have led to killing of innocent citizens and wanton destruction of valuable properties. Despite all efforts made at proffering solutions to conflicts and violence, Nigeria is yet to achieve the intended resolution. This paper focuses on investigating the use of language, religion and culture in generating a peaceful co-existence among the people of south-western Nigeria. In this research article, it was uncovered that the intended peak of conflict resolution in Nigeria is yet unattained. The research article was based on social exclusion theory and adopted a survey research design. A structured questionnaire was used to collect data from a total of 180 respondents. Data were analyzed with the use of descriptive statistics. It is expected that the research article will help Nigerians to resolve their internal conflict through the appropriate use of language, culture and religion.